Evolutionary psychology how our biology affects what we think and do - Starratt, Valerie G. (Santa Barbara, California Greenwood, an imprint of ABC-CLIO, LLO, 2016)
"From common phobias to our interactions with the opposite sex, the traits and behaviors that helped us to survive and thrive tens of thousands of years ago continue to have an impact on our thought processes, tendencies, and actions today. This fascinating reference examines the history, major themes and findings, and future direction of evolutionary psychology, a theory defined by a human being's ability to adapt and change in confluence with its environment. The work highlights contemporary debates and enduring questions in the field. Filled with fascinating insights into the mind/body connection, the book addresses the evolutionary traits that can answer questions such as "Why do people crave cheeseburgers, chips, and chocolate?", "How do men and women think about problems differently?", and "Why do people cheat?" Each chapter has thematic headings, and topics include survival, mating, parenting, culture, and religion, among others. A list of references and suggested readings after each chapter points readers toward additional sources of information"--Publisher's website.
Basic things to know -- Survival -- Mating -- Fitness and kinship -- Cognition, consciousness, and development -- Society, language, and culture -- Supernatural agency: a.k.a. of ghosts and gods -- Practical applications -- Other interesting things.
Prof. Ma. Rowena V. Mende (Recommending faculty) - Bookfair2017
Includes bibliographical references and index.
Keywords: Evolutionary psychology